PREDICTORS OF BREAST SELF-EXAMINATION UPTAKE AMONG WOMEN IN MALE’ REGION, MALDIVES - Niyaf, Aishath; AK, Sairah; Abdalqader, Mohammed (Malaysian Journal of Public Health Medicine, 2021)
Breast cancer (BC), is the most common cancer that affects women, and one of the significant causes of mortality among them. Screening and early detection of the disease are encouraged as a means of reducing mortality and enhancing the prognosis. The purpose of the study is to determine the prevalence of Breast Self-Examination (BSE) uptake and to identify the factors that are associated with the BSE uptake among Maldivian women in the Male’ region. The cross-sectional study was carried out over a period of 3 months in the Male’ region, of the Maldives. A total of 600 female citizens aged 20-79 years were selected using stratified random sampling method. Data were collected using an interviewer-administered questionnaire. About 82.70%, 54.80%, and 63.30% of the respondents had heard about BC, breast cancer screening (BCS), and BSE respectively. 50.80% of the respondents had ever performed BSE with only 22.00% performed it regularly. The significant predictors for BSE uptake were: ever heard about BC [OR=2.069, 95% CI(1.081-3.959)], ever heard about BSE [OR=2.342, 95% CI(1.326-4.137)], ever heard about clinical breast examination (CBE) [OR=1.946, 95% CI(1.117-3.390)], knowledge on early detection of BC [OR=1.077, 95% CI(1.011-1.148)], perceptions on the severity of BC [OR=1.062, 95% CI(1.010-1.116)], perceptions on barriers towards BSE [OR=0.900, 95% CI(0.846-0.958)] and self-efficacy [OR=1.112, 95% CI(1.076-1.150)]. The findings indicated that there is a pressing need for continued education and behaviour modification intervention programs using theories and models to increase women’s overall knowledge and awareness of BC and BCS and modify the long-held incorrect beliefs and misconceptions. In particular, the relevant authorities should play a proactive role in raising awareness of BC and promote BCS.